1998
DOI: 10.1021/bi9806652
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Backbone Dynamics of the Photoactive Yellow Protein,

Abstract: The solution structure of photoactive yellow protein (PYP), a photosensory protein from Ectothiorhodospira halophila, has been determined by multidimensional NMR spectroscopy. The structure consists of an open, twisted, 6-stranded, antiparallel beta-sheet, which is flanked by four alpha-helices on both sides. The final set of 26 selected structures is well-defined for the regions spanning residues Phe6-Ala16, Asp24-Ala112, and Tyr118-Val125 and displays a root-mean-square deviation, versus the average, of 0.45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 60 publications
6
59
1
Order By: Relevance
“…His-3 is located close to the protein surface, and in the crystal structure it appears not to be involved in the hydrogen bonding responsible for the closure of the N-terminal helical lariat (9). Furthermore, in solution the five residues at the N terminus of PYP are in a disordered state (36). Therefore, in the pG state of PYP, His-3 is already exposed to solvent and thus is not likely to contribute to the observed proton uptake at acidic pH.…”
Section: Discussionmentioning
confidence: 92%
“…His-3 is located close to the protein surface, and in the crystal structure it appears not to be involved in the hydrogen bonding responsible for the closure of the N-terminal helical lariat (9). Furthermore, in solution the five residues at the N terminus of PYP are in a disordered state (36). Therefore, in the pG state of PYP, His-3 is already exposed to solvent and thus is not likely to contribute to the observed proton uptake at acidic pH.…”
Section: Discussionmentioning
confidence: 92%
“…We propose that the thermodynamic fragility of the minor hydrophobic core is functionally important by priming the stimulus-induced release of the N-terminal region. NMR measurements of PYP have revealed that the two α-helices in the N-terminal region are structurally dynamic (36), suggesting that the N-terminal region is not strongly associated with the PAS domain core of PYP. This issue is relevant to signaling by PYP, because dissociation of the N-terminal region is a key event in pB formation (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the light-induced structural changes seen in LOV2 domains, light-induced structural changes at the extensions of photoreceptor domains might be a general theme, as they were observed for the so-called DAS motive of A. thaliana cryptochrome 1 [58] and a N-terminal helical segment of the photoactive yellow protein. [51,59,60] Based on these data, a model for the role of the Ja-helix of YcgF during signal transduction is proposed: In the darkadapted state the C-terminal a-helix interacts with the BLUF domain and moves upon illumination relative to the domain surface, similar to the Ja-helix of LOV2. [40] The reoriented BLUF Ja-helix could thereby affect the EAL domain's activity either by controlling access to the c-di-GMP binding site or by changing its dimeric association, [31] as EAL domains can dimerize as exemplified by the N-terminal EAL domain of YkuI from B. subtilis (2BAS).…”
Section: The Ycgf Bluf Domain and The C-terminal Ja-helixmentioning
confidence: 99%